2015
DOI: 10.1093/intqhc/mzv075
|View full text |Cite
|
Sign up to set email alerts
|

The missing evidence: a systematic review of patients' experiences of adverse events in health care

Abstract: Despite the emergence of policy initiatives to enhance patient engagement, few studies report patients' experiences of AEs. This information must be routinely captured and utilized to develop effective, patient-centred and system-wide policies to minimize and manage AEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 66 publications
7
88
0
8
Order By: Relevance
“…Other studies of patients-reported AEs highlight the wider scope in definition of an AE by patients often linked to the concept of harm 29. The narrow definition of an AE, while helpful for health services in terms of AE surveillance, potentially ignores some of the most pertinent issues surrounding AEs for patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies of patients-reported AEs highlight the wider scope in definition of an AE by patients often linked to the concept of harm 29. The narrow definition of an AE, while helpful for health services in terms of AE surveillance, potentially ignores some of the most pertinent issues surrounding AEs for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction surveys usually include rating questions about how satisfied patients feel about their care as a ‘customer’ of the service rather than asking them ‘what happened?’ 8. Berwick notes that needed service improvements can only be deduced from specific data about the nature of events as they occur; customer satisfaction ratings do not provide the in-depth evidence required 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the structures already put in place to promote patient engagement with NHS hospitals, it is disappointing how little patient involvement there appears to be in the development of ePrescribing 5. Particularly as a systematic review suggests, patients do not have the opportunity to report their experience of adverse events 6. Continuing the prescribing theme, Brennan et al report how ePresribing adoption in primary care is more likely in those countries that have a state-run registration-based primary care system such as those found in the Nordic countries and the UK 7.…”
Section: Health Informatics Has the Potential To Span The Boundaries mentioning
confidence: 99%
“…A revisão sistemática da literatura sobre a experiência dos pacientes vítimas de eventos adversos, conduzida por pesquisadores australianos, aponta o desconforto após a ocorrência, exacerbado por não receber ou receber informações inadequadas sobre os fatos e suas causas. Assim, os autores recomendam que mais estudos sejam conduzidos e que as experiências embasem a assistência centrada no indivíduo (Harrison et al, 2015).…”
Section: Discussionunclassified